Co-designing alternative frames of ageing and experiences of challenging ageism in Australia. Issue 1 (2nd January 2023) - Hausknecht, Simone; Clemson, Lindy; O'Loughlin, Kate; McNab, Justin; Low, Lee-Fay
ABSTRACT: Ageism is an ongoing pervasive issue that can be difficult to challenge. The aims of this study were to co-design alternative frames about aging in a workshop and to explore the process participants went through using these to challenge ageism in their communities over a three-month period. Participatory action research combined with co-design were used. Full-day workshops involving 27 participants across urban and regional Australia introduced participants to the concept of ageism, framing, engaging with community, and co-designing alternative frames of aging. An online group allowed participants to support each other and continue exploring ideas as they challenged ageism in their communities. After 3 months, follow-up debrief sessions involving activities and semi-structured interviews were conducted. Data from workshops (activities, recordings), online posts, and debrief sessions were analyzed. Participants found the reframing process useful for challenging aging stereotypes in the community. Over the three months they developed an increased awareness of ageism (in self, others, society) and challenged these in different ways, including changing their internal dialogue, challenging others' views on aging, and actively defying stereotypes. Five alternative frames emerged: diversity and human rights; empowerment and support; value/contributions; lifelong learning; intergenerational. The process of creating alternative frames was important and allowed participants to bring their own values andnarratives to the experience.